160k views
4 votes
Help please got to finish khan academy I’m really confused

Help please got to finish khan academy I’m really confused-example-1

1 Answer

4 votes
= 64^(t^3)*64^(-t/2)
= 64^(t^3)*(64^(-1/2))^t . . . . change the sum of exponents to a product
= 64^(t^3)*(1/√64)^t . . . . . . negative exponent signifies inverse, 1/2 power is sqrt
= 64^(t^3)/8^t . . . . . . . . . . . simplify
= (4^3)^(t^3)/8^t . . . . . . . . . .replace 64 with 4^3
= 4^(3t^3)/8^t . . . . matches the first selection only
User Abhishek Sagar
by
5.8k points